2009
DOI: 10.1179/174313209x389848
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neuropsychological functioning following temporal lobectomy in patients with temporal lobe epilepsy

Abstract: Purpose: This study was conducted to evaluate the changes in neuropsychological functioning in patients with temporal lobe epilepsy (TLE) after temporal lobe resection. Methods: Fifty-four TLE patients were evaluated before and after surgery using comprehensive neuropsychological tests to assess general intelligence, executive functioning, language, verbal and visual memory, working memory, visuo-spatial ability, attention and motor function. Results: The patients with left TLE showed no impairment of neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…As functional inadequacy of the brain to be resected is crucial to good cognitive outcome, 6) the presence of HS suggests that the ipsilateral temporal lobe was adequately dysfunctional so that the removal do not carry significant and specific risks for post-operative deterioration. 23) Patients who had undergone Lt anterior temporal lobectomy without significant sclerosis in the resected hippocampus had greater risk of deterioration in verbal memory, because the resected hippocampus had reasonably good function. 24) Therefore, our findings suggest that patients with TLE and unilateral HS have low risk for post-operative impairment in memory indices regardless of the side of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As functional inadequacy of the brain to be resected is crucial to good cognitive outcome, 6) the presence of HS suggests that the ipsilateral temporal lobe was adequately dysfunctional so that the removal do not carry significant and specific risks for post-operative deterioration. 23) Patients who had undergone Lt anterior temporal lobectomy without significant sclerosis in the resected hippocampus had greater risk of deterioration in verbal memory, because the resected hippocampus had reasonably good function. 24) Therefore, our findings suggest that patients with TLE and unilateral HS have low risk for post-operative impairment in memory indices regardless of the side of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in patients with non tumor-related intractable epilepsy showed cognitive improvement (e.g., memory or verbal fluency) with adequate seizure control after temporal resections [1016]. Less extensive resection of the mesiotemporal structures seems to correlate with better memory outcome compared with more extensive temporal lobectomy according to some groups [1719], whereas others have reported conflicting observations [2022].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with medically intractable focal epilepsy, the best option for achieving seizure control is often surgical resection . However, the benefit of epilepsy surgery must be weighed against the risk of cognitive decline, which is commonly observed in the domains of language and long‐term memory . Conversely, postsurgical gains in executive domains such as attention and working memory can be observed .…”
mentioning
confidence: 99%
“…1 However, the benefit of epilepsy surgery must be weighed against the risk of cognitive decline, which is commonly observed in the domains of language and longterm memory. 2,3 Conversely, postsurgical gains in executive domains such as attention and working memory can be observed. 4 Clinical (e.g., epilepsy duration, presurgical cognitive level) and demographic (e.g., age) factors predict postsurgical cognitive outcomes.…”
mentioning
confidence: 99%